(untitled) (The Research of Medical Science Review, 2025)
Video gaming is a popular activity among young adults, but its impact on key aspects of mental and physical well-being warrants deeper investigation. This article examines the effects of video gaming on sleep quality, social inhibition, and mental health. Drawing from empirical studies and psychological frameworks, it explores both the positive and negative consequences of gaming. The findings suggest a nuanced relationship, where gaming can enhance cognitive skills and social connectedness but may also contribute to sleep disturbances, increased social inhibition, and mental health challenges in excessive use cases. The present study examined the relationship between video gaming, sleep quality, social relation, and mental health of young adults. Moreover, the study investigated the negative effect of video gaming on sleep quality, social relation and mental health of young adults. The study was based on correlational survey research design. Participants comprised of young adults (N=120) belonged from Wah cantt, Taxila, Karachi, Rawalpindi, and Islamabad. Both males (n= 54, 45%) and females (n= 66, 55%) participated in the study. Data were collected using purposive random sampling technique. Four standardized instruments including Video Gaming Experience Questionnaire (VEQ) (Barry Dauphin & Grant Heller, 2008), Mental Health Screening Questionnaire (Sharma P & Devkota G, 2019), Sleep Quality Scale and Sleep Variables Questionnaire (SQS) (Chol Shin, 2012), Social Inhibition Scale (Gronbach's, 2018) were used for data collection. Correlation matrices & Linear regression analysis was applied for testing the hypothesis. Video gaming is positively correlated with Sleep quality (r = .39, P<.01), Social inhibition (r = .40, P< .01) and Mental health (r = .28, P< .01). Video gaming positively predicted Sleep quality (β = .39, p < .001), Sleep inhibition (β = .40, p < .001), mental health (β =.28, p < .001). The findings revealed that there is positive correlation and video gaming has great impact on sleep, social inhibition and mental health of young adults.